Features of Tasks in the Process of Implementation Engineering Changes in the Automotive Industry: Manager’s Point of View - Lukasz Hadas; Hubert Wojciechowski (Communications of International Proceedings, 2021)
Aim: The article presents selected features of tasks in the process of implementing engineering changes in the automotive industry from a managerial point of view. The research problem concerns the identification of features in tasks. Selection of tasks that are useful in the process of managing the implementation of engineering changes. The last part of research problem covers frequency of features in all of 53 tasks and grouping those tasks in categories according to material scope. Methodology: The results of the study are a part of a broader research on the management of the process of implementing changes in the components of the automotive industry. The research process included the following steps: in-depth interview with experts with experience in management (planning, coordination, supervision and evaluation) draft technical changes, prepare a list of selected features and their definitions, preparation of a questionnaire for the CAWI survey and analysis of results. Findings: The obtained research results allowed to determine that, in the opinion of practitioners, the features of tasks useful in the process of managing the implementation of engineering changes can be: “Time-consuming”, “Labour-intensive”, “Expensive”, “Complicated”, “Routine (repeatable)”. Then, a description of each of the 53 tasks based on the indication of the respondents was obtained. Conclusions: Extending the knowledge about selected features for tasks performed during the implementation of engineering changes can supports the management process in such aspects as: works schedule preparation, resource allocation, cost estimation or location of time or resource buffers.
Keywords: Project Management; Engineering Changes; Automotive Industry; Change Management